Practical Aspects of Teaching Implicature Translation - Sharipova , Charos (The Lingua Spectrum, 2025)
Translation activity requires not only the literal transfer of text from one language to another but also the consideration of cultural, contextual, and pragmatic aspects. The main task of a translator is not only to know languages but also to understand the nuances of both cultures and ensure the preservation of the purpose and meaning of the text. Since each language has its unique styles of expression, idiomatic phrases, and cultural characteristics, it is essential not to distort the essence and meaning of the original text during the translation process. This article examines the practical aspects of teaching students to translate implicatures. Implicature refers to the meaning that is not explicitly stated in speech but is implied in the context. This process is a complex task for students, and teaching it requires methods such as contextual analysis and consideration of cultural and pragmatic aspects. The article outlines the difficulties encountered in the process of translating implicatures and analyzes the practical aspects of teaching students to translate implicatures, namely the methods, tasks, and exercises used in the learning process. Teaching students the specific features of implicatures in the translation process plays a significant role in developing their linguo-pragmatic competence.